2013
DOI: 10.1080/10934529.2013.729998
|View full text |Cite
|
Sign up to set email alerts
|

Structure-dependent lipid peroxidation by photoirradiation of pyrene and its mono-substituted derivatives

Abstract: Pyrene, one of the most studied polycyclic aromatic hydrocarbons can damage biological macromolecules and cause toxicity when irradiated by light. The effect of substituents, 1-amino, 1-hydroxy, 1-nitro, and 1-bromo, on light-induced lipid peroxidation is studied. Degradation kinetics and photoproduct analyses were conducted to test how these substituents affect the photoreaction. All five compounds have different photodegradation rates, and these rates parallel their light absorptivity. Four out of the five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Our results further confirm the ability of 1-NP to induce ROS generation because the compound induced protein oxidation and, to a lesser extent, lipid peroxidation. There have been reports on the induction of lipid peroxidation by 1-NP in various experimental systems, including rat hepatocytes, mouse hepatoma cells and methyl linoleate [ 33 , 34 , 35 ]. However, our study is the first demonstrating the ability of 1-NP to induce oxidative damage to macromolecules other than DNA in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further confirm the ability of 1-NP to induce ROS generation because the compound induced protein oxidation and, to a lesser extent, lipid peroxidation. There have been reports on the induction of lipid peroxidation by 1-NP in various experimental systems, including rat hepatocytes, mouse hepatoma cells and methyl linoleate [ 33 , 34 , 35 ]. However, our study is the first demonstrating the ability of 1-NP to induce oxidative damage to macromolecules other than DNA in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…As pyrene exhibits characteristic absorption spectra in the UV-region, pyrene UV absorption spectra was used to determine the critical micellar concentration in different surfactant solutions 38 . Because of its highly conjugated nature as an aromatic molecule, pyrene has several absorption bands extending from 200 to 360 nm 39 . The equilibrium water content of the hydrogels was measured to ensure uniformity 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to its greater photo-stability 8 and higher intersystem crossing yield, 1-BP produces more triplet excited state species 38 . These longer-lived triplet state species of 1-BP can generate more singlet oxygen than any of the other four compounds.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that damages to cellular constituents DNA, protein and lipids are the main reasons leading to phototoxicity 6,7 . In a recent study, we reported that light-induced lipid peroxidation by 1-substituted pyrenes are strongly structure dependent 8 . Although any form of damage to the cell can lead to cellular death, DNA damages may be repaired and the cellular function may be partially or even fully restored.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation